Leadership and Social Harmony: Understanding the Leader's Role in Fostering Social Integration Within Coastal Islamic Communities - Ries Dyah Fitriyah (Millati: Journal of Islamic Studies and Humanities, 2024)
This paper aims to explore the role of local leaders in fostering social harmony within conflict-prone coastal Muslim communities, primarily composed of fishermen. The focus is on how local leaders promote social harmony while navigating the challenges, priorities, and opportunities they face. It is essential to consider the diverse nature of these communities. Although they may appear united due to their shared livelihood, the realities are often more complex, featuring intricate social dynamics, power structures, and competing interests. The research was conducted in Kalirejo Village, located in the Kraton District of Pasuruan. This location was chosen due to its history of significant conflict dynamics; however, the community is currently peaceful, largely owing to the diligent efforts of local leaders in promoting peace. This study employs qualitative research methods, utilizing data collection techniques such as observation, interviews, and focus group discussions. The findings indicate that local leaders have implemented four key strategies to promote social harmony in coastal Muslim communities. First, they have engaged in mediation and negotiation efforts. Second, they actively appeal to the community to prevent further conflict during events. Third, they serve as guarantors for individuals involved in conflicts before legal proceedings. Lastly, they organize activities that involve both parties, such as Friday Tours and grand religious studies.